A Comparative Study of Financial Performance During and After the Covid-19 Pandemic in Food and Beverage Companies - Salsabila, Firdaus; Muslimin, Muslimin (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
A This study aims to measure financial performance through comparisons during and after COVID-19, specifically for food and beverage business entities listed on the Indonesia Stock Exchange. The research method is comparative, comparing financial ratios during the pandemic (2020-2021) and post-pandemic (2022-2023). The study used a sample of 16 companies that met the standards as research units. The results showed that the current ratio showed no significant change, the return on investment ratio showed a significant change, namely an increase in investment value after the pandemic, and the inventory turnover ratio did not experience a significant change in financial performance.